Jenis dan Fungsi Satire dalam pantun Aceh di Aceh Utara - Nurhaliza Nurhaliza; Radhiah Radhiah; Maulidawati Maulidawati (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
This research aims to describe the types and functions of satire in Acehnese pantun in North Aceh. This research approach is qualitative with descriptive research type. The research data consists of rhymes that exist in North Aceh society, with data sources taken from the community in Muara Batu District. The types of satire in pantun are divided into two categories: Horatian (soft) satire and juvenalian (hard) satire. The function of satire in pantun is grouped into lessons, humor and social criticism. Data collection techniques used include interviews, recording and recording. The data analysis stages are carried out through data reduction, data presentation, and drawing conclusions. The results of the research showed that of the 27 pantun data found, there were 18 pantuns with Horatian satire and 9 pantuns with juvenalian satire. Satire in Acehnese pantun in North Aceh functions as social criticism (17 rhymes), humor (1 rhymes), and lessons (9 rhymes). This research provides an overview of the use and function of satire in Acehnese pantun, which reflects the rich culture and social values contained in North Aceh society.